Myeloproliferative disease in children: a demographic study. Issue 8 (August 1988) - Reid, M M; Saunders, P W; Kernahan, J
Abstract : Over eight years, eight cases of childhood myeloproliferative disease were recognised in the northern region of England (population 3.1 million). Five were classic chronic myeloid leukaemia (CML) and the three others, forms of myeloproliferative disease. No case of juvenile CML was recognised. With the exception of CML, "adult" type myeloproliferative disease of children is underrepresented in the literature and its natural history remains unknown.